2014
DOI: 10.1071/ch13713
|View full text |Cite
|
Sign up to set email alerts
|

Novel Synthesis, Molecular Structure, and Theoretical Studies of Dispiro Compounds via Pseudo-eight-component Reaction

Abstract: We have developed a diastereoselective synthesis of dispiro compounds through a one-pot domino pseudo-eight-component reaction of amines, aldehydes, and Meldrum’s acid. This method resulted in the generation of complex products with four stereocentres and involves formation of 10 new bonds. Quantum mechanical calculations were undertaken in order to determine the stability of the eight diastereomer structures of compound 4a. The crystal structure of 4k was determined by X-ray crystallography. Reaction mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In 2014, Hazeri and co-workers 92 reported a diastereoselective synthesis of poly-substituted hydroquinolines via a one-pot domino pseudo-8CR, using three equivalents of Meldrum's acid ( 600 ), four equivalents of aromatic aldehydes 601a–h , aromatic amines 605a–e , in acetonitrile in the presence of trichloroacetic acid. A reaction mechanism was proposed as Scheme 61 depicts.…”
Section: Pseudo-seven Component Reactions and Morementioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, Hazeri and co-workers 92 reported a diastereoselective synthesis of poly-substituted hydroquinolines via a one-pot domino pseudo-8CR, using three equivalents of Meldrum's acid ( 600 ), four equivalents of aromatic aldehydes 601a–h , aromatic amines 605a–e , in acetonitrile in the presence of trichloroacetic acid. A reaction mechanism was proposed as Scheme 61 depicts.…”
Section: Pseudo-seven Component Reactions and Morementioning
confidence: 99%
“…Abaee and co-workers 31 reported the synthesis of a collection of dicyanoanilines fused to a dithiane ring via a facile and efficient reaction among aldehydes 91a-j, 1,3-dithia-5-one (92), two equivalents of malononitrile (93) and triethylamine as catalyst. The proposed mechanism is depicted in Scheme 12.…”
Section: Knoevenagel Condensation/michael Additionmentioning
confidence: 99%
“…This method resulted in the generation of complex products with four stereocentres and involves formation of 10 new bonds. [10] In our study to synthesize complex molecules using concise protocols, we found that substituted spiro [5,5]undecane-1,5,9-triones could be easily obtained from the reaction of equal equivalent amounts of aromatic aldehydes and Meldrum's acid using aniline as a catalyst. In particular, this approach is different from previous reports that gave cis-substituted products.…”
Section: Introductionmentioning
confidence: 98%
“…Recent works by Maghsoodlou and co-workers exhibited that phthalic acid was also capable of catalyzing the pseudo-six-component reaction of Meldrum’s acid, benzaldehyde derivatives, and aniline derivatives to afford polysubstituted hydroquinoline derivatives under mild reaction conditions (Scheme ). , The difference between the current research and the prominent work presented by Maghsoodlou et al is that the current reaction utilizes 2 equiv of Meldrum’s acid, 3 equiv of benzaldehyde derivatives, and 1 equivalent of amine derivatives to yield new structures.…”
Section: Introductionmentioning
confidence: 99%